2015
DOI: 10.1590/0001-3765201520140154
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic and organic trace mineral supplementation in weanling pig diets

Abstract: A study was conducted to evaluate the effects of dietary inorganic and organic trace minerals in two levels of supplementation regarding performance, diarrhea occurrence, hematological parameters, fecal mineral excretion and mineral retention in metacarpals and liver of weanling pigs. Seventy piglets weaned at 21 days of age with an average initial body weight of 6.70 ± 0.38 kg were allotted in five treatments: control diet (no added trace mineral premix); 50% ITMP (control diet with inorganic trace mineral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…However, none of the four groups showed a higher incidence of diarrhea than the others. Thomaz et al [38] report that animals fed diets supplemented with trace minerals in inorganic form suffer higher rates of diarrhea than animals fed diets without mineral supplements. However, this was not confirmed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the four groups showed a higher incidence of diarrhea than the others. Thomaz et al [38] report that animals fed diets supplemented with trace minerals in inorganic form suffer higher rates of diarrhea than animals fed diets without mineral supplements. However, this was not confirmed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement, Martin et al [ 13 ] evaluated the OTM and ITM supplementation from weaning to 35 d postweaning and demonstrated that iron sulfate deposited more Fe in liver than organic (chelated) source of Fe but not in kidney. A recent trial conducted by Thomaz et al [ 20 ] indicated that iron sulfate fed pigs have more liver Fe than Fe proteinate fed pigs for an inclusion rate at 100% of requirement but similar liver Fe at 50% requirements for nursery (postweaning to 42 d) pigs. In an early study by Standish and Ammerman [ 21 ], excess Fe as ferrous sulfate or ferric citrate fed to sheep increased liver and spleen Fe dramatically, but the muscle Fe was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…One of the points that should be noted in the methodology when studying chelated minerals is the recommended nutritional level. Many studies indicate that, due to increased bioavailability, lower levels of chelated minerals (compared to saline sources) would be sufficient to meet the animals' requirements [5,14,16,17]. Perhaps this explains the absence of difference in the performance of sows fed with organic and inorganic Ca sources in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…There is quite extensive research on the benefits of chelated mineral sources in animal nutrition, in particular for non-ruminants [14][15][16][17]. These associated mineral sources have been reported to improve mineral absorption, and when replacing traditional inorganic mineral sources are capable of maintaining or improving performance [14,15].…”
Section: Discussionmentioning
confidence: 99%